Mesenchymal Stromal Cells Are More Immunosuppressive In Vitro If They Are Derived from Endometriotic Lesions than from Eutopic Endometrium - Fawaz Abomaray; Sebastian Gidlöf; Cecilia Götherström (Stem Cells International)
Endometriosis is an inflammatory disease with predominance of immunosuppressive M2 macrophages in the pelvic cavity that could be involved in the pathology through support and immune escape of ectopic lesions. Mesenchymal stromal cells (MSC) are found in ectopic lesions, and MSC from nonendometriosis sources are known to induce M2 macrophages. Therefore, MSC were hypothesized to play a role in the pathology of endometriosis. The aim was to characterize the functional phenotype of MSC in ectopic and eutopic endometrium from women with endometriosis. Stromal cells from endometriotic ovarian cysts (ESCcyst) and endometrium (ESCendo) were examined if they exhibited a MSC phenotype. Then, ESC were phenotypically examined for protein and gene expression of immunosuppressive and immunostimulatory molecules. Finally, ESC were functionally examined for their effects on monocyte differentiation into macrophages. ESCcyst and ESCendo expressed MSC markers, formed colonies, and differentiated into osteoblasts and adipocytes. Phenotypically, ESCcyst were more immunosuppressive, with significantly higher expression of immunosuppressive molecules. Functionally, ESCcyst induced more spindle-shaped macrophages, with significantly higher expression of CD14 and CD163, both features of M2 macrophages. The results suggest that ESCcyst may be more immunosuppressive than ESCendo and may promote immunosuppressive M2 macrophages that may support growth and reduce immunosurveillance of ectopic lesions.